2013
DOI: 10.1002/jgrd.50143
|View full text |Cite
|
Sign up to set email alerts
|

Northern Hemisphere blocking frequency and duration in the CMIP5 models

Abstract: [1] Northern Hemisphere (NH) blocking climatology is examined using a subset of climate models participating in the Coupled Model Intercomparison Project phase 5 (CMIP5). Both historical and Representative Concentration Pathway (RCP) 8.5 integrations are analyzed to evaluate the performance of the CMIP5 models and to identify possible changes in NH blocking frequency and duration in a warmer climate. Comparison with reanalysis data reveals that CMIP5 models can reproduce the NH blocking climatology reasonably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
96
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 34 publications
19
96
2
Order By: Relevance
“…In contrast to the findings of Dunn-Sigouin and Son (2013) and Masato et al (2013), Cattiaux et al (2013) found an increase in the frequency of blocking events in the Atlantic-European sector during summer for most of the 19 CMIP5 models considered. The other two studies considered simulations from fewer CMIP5 models and used various indices to define blocking, while Cattiaux et al (2013) used an approach based on weather regimes, with blocking being one of them.…”
Section: Atmospheric Blockingcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the findings of Dunn-Sigouin and Son (2013) and Masato et al (2013), Cattiaux et al (2013) found an increase in the frequency of blocking events in the Atlantic-European sector during summer for most of the 19 CMIP5 models considered. The other two studies considered simulations from fewer CMIP5 models and used various indices to define blocking, while Cattiaux et al (2013) used an approach based on weather regimes, with blocking being one of them.…”
Section: Atmospheric Blockingcontrasting
confidence: 99%
“…The CMIP5 simulations for the high RCP8.5 scenario show an overall decrease in the frequency of atmospheric blocking in the Atlantic-European sector in both winter (Cattiaux et al 2013;Dunn-Sigouin and Son 2013;Masato et al 2013) and summer (Dunn-Sigouin and Son 2013;Masato et al 2013). The decrease in summer is accompanied by an increase on its eastern flank, leading to an eastward shift of the area with high blocking frequencies (Masato et al 2013).…”
Section: Atmospheric Blockingmentioning
confidence: 98%
“…Hence, blocking research mainly relies on model output and reanalysis data rather than using direct observations. However, most models show only limited skill in blocking representation, as has been noted by many studies in the past (D'Andrea et al, 1998;Vial and Osborn, 2012;Barnes et al, 2012;Anstey et al, 2013;Christensen et al, 2013;Dunn-Sigouin and Son, 2013;Masato et al, 2013). Recently, Davini and D'Andrea (2016) showed that current climate models still underrepresent blocking occurrence by up to 50 %, particularly in the Euro-Atlantic blocking region.…”
Section: Introductionmentioning
confidence: 95%
“…Also displayed is the area averaged RMSE for 10-90N 1 3 and up to weeks, their impact on the weather and climatology of a region is large. The frequency of atmospheric blocking tends to be underestimated by GCMs (Anstey et al 2013;Masato et al 2013;Dunn-Sigouin and Son 2013;D'Andrea et al 1998). Figure 8 shows the annual and seasonal blocking frequencies in the Northern Hemisphere.…”
Section: Blockingmentioning
confidence: 99%